PET Radiopharmaceuticals for Imaging Integrin Expression: Tracers in Clinical Studies and Recent Developments. (11th June 2014) - Haubner, Roland; Maschauer, Simone; Prante, Olaf
Abstract : Noninvasive determination of integrin expression has become an interesting approach in nuclear medicine. Since the discovery of the first 18 F-labeled cyclic RGD peptide as radiotracer for imaging integrin α v β 3 expression in vivo, there have been carried out enormous efforts to develop RGD peptides for PET imaging. Moreover, in recent years, additional integrins, including α 5 β 1 and α v β 6, came into the focus of pharmaceutical radiochemistry. This review will discuss the tracers already evaluated in clinical trials and summarize the preliminary outcome. It will also give an overview on recent developments to further optimize the first-generation compounds such as [ 18 F]Galacto-RGD. This includes recently developed 18 F-labeling strategies and also new approaches in 68 Ga-complex chemistry. Furthermore, the approaches to develop radiopharmaceuticals targeting integrin α 5 β 1 and α v β 6 will be summarized and discussed.